Análise do processo de construção e desconstrução das garantias laborais do Brasil: o modelo protetivo dos anos 1930 e a reforma trabalhista de 2017 - Carvalho, Leandro de Andrade (2020)
Labor guarantees are indissoluble from development policies. If the 1930s represented the beginning of the industrialization and the formation of the domestic consumer market in Brazil, its framework of work valuation reflected a model that had lasted for fifty years. With its exhaustion, the erosion of work conditions was introduced in the 1990s as a neoliberal response to the State’s withdrawal from both the economy and the relations between employers and employees. These policies were softened during the first fifteen years of the 21st century, which brought symbolic victories for the working class. Nevertheless, this period precedes a new conservative resumption, which culminated in the 2017 Labor Reform. Taking this historical background into account, this dissertation aims at analyzing the main changes in the work context from 1930 to 2017. For this, a broad literature review has been carried out and secondary data about the Brazilian labor market has been used. In addition, the analysis of the main changes in the Brazilian labor legislation and their impacts in the country’s economic development has been conducted. Results show that the 2017 Labor Reform has redeemed the policies implemented in the 1990s, but with greater losses for the working class.